A imputação nos crimes omissivos impróprios - Leite, Luciana de Brito Freitas (2011)
Criminalization has Primary diurnal covering crimes omissive, requiring your further study. The omission can not always be typed in all its aspects, therefore, the existence of crimes omissive is inappropriate given that reprehensible attitudes do not go unpunished. The crimes may occur through action and omission. The omission, as shown in this study, is classically divided into proper and improper. Those are expressly provided for by law and these require matching clause. Omissive crimes can be distinguished by their crimes commissive elements. The position ensures attention has been paid in the present study, in order to consolidate the cases in which a person really must answer the inaction.